Factors associated with schizophrenia among outpatients - Annuur, Mutia Diah; Warni, Hernida; Rahman, Aulia (JOURNAL OF Mental Health Concerns, 2026)
Background: Schizophrenia is a chronic and severe mental disorder that affects thinking, perception, emotion, and behavior. The increasing number of mental disorder cases in the working area, highlights the importance of identifying factors associated with the incidence of schizophrenia. Purpose: To determine the association between family/genetic history, personality type, parenting style, and family disharmony with the incidence of schizophrenia among outpatients. Method: A quantitative approach with a case-control design. The population consisted of all outpatients registered at Kedaton Primary Health Center in 2026. A total of 104 respondents were selected as samples, consisting of case and control groups with a 1:1 ratio. The sampling technique used was purposive sampling based on predetermined inclusion and exclusion criteria. Data were collected using structured questionnaires and analyzed through univariate and bivariate analysis using the Chi-Square test. Results: Family/genetic history was significantly associated with the incidence of schizophrenia (p=0.001). Meanwhile, personality type (p=0.845), parenting style (p=0.130), and family disharmony (p=0.072) were not significantly associated (p>0.05). Respondents with a family history of schizophrenia had a higher risk of developing schizophrenia compared to those without such history. Conclusion: Genetic factors were significantly associated with schizophrenia in this study. Strengthening early detection and family-based mental health education at the primary health care level is essential to reduce the risk of schizophrenia in the community. Keywords: Family Disharmony; Family History; Parenting Style; Personality Type; Schizophrenia.